1990
DOI: 10.1108/eb047071
|View full text |Cite
|
Sign up to set email alerts
|

Image handling for museums and libraries: report of a conference

Abstract: The British Library Research and Development Department (BLR &DD) has long been interested in the developing technologies in the fields of imaging and multimedia, and in 1988 published An overview of image processing and image management systems and their application. This report reviewed several fields where these technologies were already being used and also highlighted the future trends for the industry and standards. Since then imaging and multi‐media projects with relevance to the library and informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
1995
1995

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Another Italian initiative has adopted a similar approach in the particular context of astronomical image data (Bordogna, Carrara, Gagliardi, Merelli, Mussio, Naldi, & Padula, 1990). An extension has been proposed to the automatic feature extraction work undertaken by Stonham, mentioned above, which would seek to effect automatic, content-based retrieval of images in response to textual queries (Stubley, 1990;Enser, 199 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another Italian initiative has adopted a similar approach in the particular context of astronomical image data (Bordogna, Carrara, Gagliardi, Merelli, Mussio, Naldi, & Padula, 1990). An extension has been proposed to the automatic feature extraction work undertaken by Stonham, mentioned above, which would seek to effect automatic, content-based retrieval of images in response to textual queries (Stubley, 1990;Enser, 199 1).…”
Section: Resultsmentioning
confidence: 99%
“…Its 1990 annual Anglo-French seminar was devoted to image handling for museums and libraries, and active researchers in the field were invited to present position papers which covered a broad spectrum of image retrieval applications. A review may be found in Stubley (1990). In addition, the Department organized an international research conference on multimedia information in 199 1, and published the proceedings (Feeney & Day,199 1).…”
Section: British Library Research and Development Department Imaging mentioning
confidence: 99%
See 1 more Smart Citation